The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/cancers15102722
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the p16 and p53 Tumor Suppressor Proteins and Viral HPV16 E6 and E7 Oncoproteins in the Assessment of Survival in Patients with Head and Neck Cancers Associated with Human Papillomavirus Infections

Abstract: The role of HPV in the survival prognosis of patients with head and neck squamous cell carcinoma, especially patients with laryngeal squamous cell carcinoma (LSCC) and hypopharyngeal squamous cell carcinoma (HPSCC), is still somewhat ambiguous. The present study aimed to explore the significance of tumor suppressor proteins and HPV16 E6 and E7 oncoproteins in the assessment of survival in patients with oropharyngeal squamous cell carcinoma (OPSCC), LSCC, and HPSCC associated with high-risk (HR-) and low-risk (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 74 publications
(95 reference statements)
0
2
0
Order By: Relevance
“…In response to this disruption, cells increase the production of p16 to counteract uncontrolled progression of the cell cycle [45,46]. Therefore, p16 overexpression is an indirect result of HPV oncogenic activity within the cell [47]. Because p16 overexpression is closely linked to the disruption of cell cycle control by high-risk HPV types, it serves as a surrogate marker of HPV-associated oncogenic activity [48].…”
Section: P16/ki-67 Dual Staining: An Emerging Tool For Triagementioning
confidence: 99%
“…In response to this disruption, cells increase the production of p16 to counteract uncontrolled progression of the cell cycle [45,46]. Therefore, p16 overexpression is an indirect result of HPV oncogenic activity within the cell [47]. Because p16 overexpression is closely linked to the disruption of cell cycle control by high-risk HPV types, it serves as a surrogate marker of HPV-associated oncogenic activity [48].…”
Section: P16/ki-67 Dual Staining: An Emerging Tool For Triagementioning
confidence: 99%
“…Many studies have confirmed that HPV mainly combines with the tumor suppressors p53 and pRB through the E6 and E7 proteins to cause uncontrolled cell proliferation, resulting in damage or even loss of cellular DNA self-repair function, leading to cancer. 7 , 8 , 9 , 10 The characteristic of HPV E6 protein is that it has two structural domains, which contain zinc finger structures, and these zinc finger structures bind to DNA and RNA and mediate protein-protein interactions to realize the cell transformation of E6 protein. 11 The E6 protein mainly causes mutations in the tumor suppressor gene p53 and binds to the p53 protein, leading to its inactivation and degradation of the p53 protein, thereby causing malignant expansion of cells.…”
Section: Introductionmentioning
confidence: 99%
“…This integration results in uncontrolled replication of human papillomavirus oncoproteins and the release of pro-inflammatory molecules, and both together eventually cause chronic inflammation and the degradation of the tumor suppressor gene p53. Therefore, chronic inflammation is responsible for the progression of cervical dysplasia to cancer and HPV-mediated cancers [5,6].…”
Section: Introductionmentioning
confidence: 99%